Pengaruh Edukasi Stimulasi Terhadap Perkembangan Kognitif Anak Usia Dini di Sekolah Tk Kartika XXI-17 Gorontalo - Rabiatul Adawiya Lapasu; Triassetiawaty Dade; Prahara M. Marjuni; Pupung Puspa Ardini; Sri Rawanti (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
Early childhood cognitive development is an important foundation for successful learning and further development. One of the factors that significantly influences this development is structured and continuous stimulation education. This study aims to analyze the effect of stimulation education on cognitive development in Kartika XXI-17 Kindergarten. Cognitive ability is the child's ability to think more complexly and to reason and solve problems, the development of this cognitive ability will make it easier for children to master broader general knowledge, so that they can function properly in everyday community life. However, in its development, not all children in Kartika XXI-17 Kindergarten can develop according to their stages. Stimulation education has been proven to be more effective when carried out early, with an approach that is appropriate to the child's developmental stage. In conclusion, stimulation education plays a crucial role in accelerating and optimizing the cognitive development of early childhood, so it needs to be an integral part of child care and education practices.